Religious Education Learning Evaluation Planning SMP Negeri 1 Sungai Raya Kubu Raya District In 2024 - Kasiono; Hasyim Hadadde; Baharuddin; Hifza (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The purpose of this study was to describe the planning of religious education learning evaluation at SMP Negeri 1 Sungai Raya Kubu Raya Regency in 2024. The research method used was qualitative research method. Data and data sources consist of primary and secondary data obtained from interviews, observations, field notes. The primary data sources are respondents who respond or answer researchers' questions, both in the form of oral and written questions given to teachers, principals, school supervisors and students of SMP Negeri 1 Sungai Raya Kabupaten Kubu Raya Year 2024. While secondary data sources in this study are in the form of documents or records related to the research that researchers are doing. The results showed that; First, the planning of religious education learning evaluation at SMP Negeri 1 Sungai Raya, Kubu Raya Regency using the CIPP Model (Context, Input, Process, Product) includes several systematic stages. At the Context stage, a situational analysis is conducted to understand the needs, objectives, and learning standards that must be achieved. The Input stage involves identifying available resources, such as teacher qualifications, facilities and learning materials, as well as gathering information about the curriculum and teaching methods. Evaluation begins with the identification of needs and standards of success to establish the learning context. The input stage involves reviewing existing resources, curriculum and lesson plans. Then, in the process stage, the implementation of teaching is observed and monitored to ensure conformity with the plan while measuring active student participation and the effectiveness of teaching methods. Finally, in the product stage, student learning outcomes are thoroughly evaluated using a variety of assessment methods, with analyzed results providing feedback for continuous improvement. The CIPP model ensures a comprehensive evaluation from process to educational outcomes for the improvement of learning quality.